2021
DOI: 10.1002/poc.4310
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of photoconversion of cyclic dinitrone to oxaziridine and dioxaziridine: A computational investigation of an experimentally reported photochemical reaction

Abstract: The unexplored photochemistry behind the conversion of cyclic dinitrone to oxaziridine and dioxaziridine has been investigated computationally. The mechanism behind the experimentally reported photo‐conversion reaction of 2,2,4,5‐tetramethyl‐2H‐imidazole‐1,3‐dioxide has been analyzed. The allowed S0‐S1 transition in this cyclic dinitrone system is characterized by a transition moment value of 3 Debye. The photo‐excitation to the vertically excited S1 state is subsequently followed by a passage through low‐lyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It can be added here that in the last few decades, several photochemical reactions have been reported where the involvement of CIs have been found [14–35] . In our earlier studies on the cyclic nitrone systems, [11–13] we have studied various pyrroline 1‐oxide and 2H‐imidazole‐1,3‐dioxide systems. There remains huge scope to explore the mechanism of the photochemistry of the substituted 2H‐imidazole 1‐oxide systems.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It can be added here that in the last few decades, several photochemical reactions have been reported where the involvement of CIs have been found [14–35] . In our earlier studies on the cyclic nitrone systems, [11–13] we have studied various pyrroline 1‐oxide and 2H‐imidazole‐1,3‐dioxide systems. There remains huge scope to explore the mechanism of the photochemistry of the substituted 2H‐imidazole 1‐oxide systems.…”
Section: Introductionmentioning
confidence: 95%
“…In the recent years, our group has been actively involved in the investigations on the photochemistry of nitrones. In addition to the acyclic nitrone systems, in recent years, we have also proposed [10–13] the possible photo‐isomerization mechanisms for most of the above‐mentioned cyclic nitrone systems through quantum mechanical investigations. These studies have indicated that the nitrone to oxaziridine conversion process goes through a low‐lying S 0 /S 1 conical intersection (CI).…”
Section: Introductionmentioning
confidence: 99%
“…During the last 5 years, Chattopadhyay et al [38][39][40][41] have investigated the photo-isomerizations and lactam formations of several cyclic N-oxide systems which include methyl-substituted pyrroline 1-oxides and 2H-imidazole N-oxides. These computational investigations have put forward the explanations of several unanswered questions related to the photochemistry and thermal reactions of these cyclic nitrones and nitrone-like compounds.…”
mentioning
confidence: 99%